Work-life balance di era new normal pada pekerja wanita - Lintar Niendhya Milleniva; Tri Muji Ingarianti; Nandy Agustin Syakarofath (Fakultas Psikologi, 2023)
New normal has changed the way people live and work which has an impact on work and family life, especially female workers who are considered to be the most experiencing difficulties in work-life balance which can cause problems with work-life balance. The purpose of this study is to show 1) a description of the views or perceptions of female workers regarding work-life balance, 2) the psychological dynamics of female workers in balancing work-life in WFH and WFO situations, 3) the problems faced by female workers both internally and externally in achieving life balance. work in the new normal era, 4) adaptation of female workers to WFH and WFO situations and 5) strategies used to achieve work-life balance in the new normal . This study uses qualitative method with phenomenological approach. The subjects of this study were 5 female workers who were taken by snowball sampling technique using qualitative analysis using the Miles and Huberman models. The results show that female workers view work-life balance in the new normal as a positive thing. In work-life balance tends to have a negative impact on psychology. Post-pandemic changes (new normal) make female workers have to do multitasking resulting in problems in work-life balance. Adapting to WFH and WFO situations of female workers feel positive in work-life balance, which both internally and externally are very supportive to achieve work-life balance. The results of the above study also explain that female workers have effective strategies in work-life balance. Keywords: Female workers, new normal, work-life balance